SOSIALISASI TANGGAP RABIES MELALUI PENDEKATAN MASYARAKAT DI DESA KUALIN, KABUPATEN TIMUR TENGAH SELATAN - Pandarangga, Putri; Utami, Tri; Foeh, Nancy Diana Frederika Katerina; Sitompul, Yeremia Yobelanno; Wuhan, Yustinus Oswin Primajuni; Simarmata, Yohanes Timbun Raja Mangiut Ronael; Joesoef, Jayusman Arsiyanti; Datta, Frans Umbu; Amalo, Maria; Dangur, Fransiska Aping (Universitas Nusa Cendana, 2024)
Rabies is a zoonotic disease that can attack humans through dog bites. Various methods have been performed for prevention, including socialization activities about rabies. The aim of community service, conducted by the Clinical, Reproduction, Pathology, and Reproduction Laboratory, Faculty of Medicine and Veterinary Medicine, Nusa Cendana University in Kualin Village, was to increase knowledge about rabies. Socialization was a method to increase awareness about rabies in the Kualin community, which this method using the Asset Based Community Development (ABCD) approach. The ABCD concept consists of 1). Identification of community assets; 2). Partner involvement; 3). Participation of the community service team; and 4). Partnership collaboration. The poster was one of the communication, information, and education (KIE) tools for transferring knowledge. Based on the results of the pre-and post-test, it shows that this method is quite successful where public knowledge about the symptoms of animals infected with rabies (58.82% to 88.23%), symptoms of humans infected with rabies (35.29% to 76.47%), and assistance if bitten by infected dogs (76.47% to 88.23%) increased significantly. So, this method can be applied to socialize other animal diseases that cause economic losses to the Kualin community.